UPAYA PELESTARIAN PENCAK SILAT UPAYA PELESTARIAN PENCAK SILAT DAN WISATA BANTEN LAMA BERBASIS DIGITAL MARKETING GUNA MELESTARIKAN WARISAN BUDAYA DI KOTA SERANGPROVINSI BANTEN - Ranthy Pancasasti Pancasasti; Pranajaya Kusuma; Sri Ndaru Arthawati; Tris Sudarto (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
This community service activity (PPM) was carried out in Serang City in partnership with the Assyfa Pencak Silat Padepokan and the Manager of Old Banten Tourism Places, namely Explore Banten Travel. Serang City as the capital of Banten Province holds various artistic, cultural and tourist potentials, which if managed properly, can generate large income for the community and the government of Serang City. For example, Pencak Silat and Banten Lama tourism which is one of the historical heritage of the people of Banten. On the other hand, there are still many people and tourists (local and foreign) who do not know about Pencak Silat and Banten Lama tourism. So it is deemed necessary to hold a community service program (PPM) in the form of socialization and education about Pencak Silat and Old Banten tourism so that it remains sustainable and known to foreign countries. The method used in this PPM is in the form of socialization and education based on digital marketing through social media. The results of this PPM are in the form of documentary films on the YouTube Channel and content on social media about Pencak Silat and Banten Lama tourism, in order to participate in helping government programs, promoting Pencak Silat and Banten Lama tourism so that they remain sustainable and are known to foreign countries.